Glucocorticoid receptor β and histone deacetylase 1 and 2 expression in the airways of severe asthma. Issue 5 (8th December 2011) - Butler, Claire A; McQuaid, Stephen; Taggart, Cliff C; Weldon, Sinead; Carter, Richard; Skibinski, Grzegorz; Warke, Timothy J; Choy, David F; McGarvey, Lorcan P; Bradding, Peter; Arron, Joe R; Heaney, Liam G
Abstract : Rationale: Upregulation of glucocorticoid receptor β (GRβ) has been implicated in steroid resistance in severe asthma, although previous studies are conflicting. GRβ has been proposed as a dominant negative isoform of glucocorticoid receptor α (GRα) but it has also been suggested that GRβ can cause steroid resistance via reduced expression of histone deacetylase 2 (HDAC2), a key regulator of steroid responsiveness in the airway. Objectives: To examine GRβ, GRα, HDAC1 and HDAC2 expression at transcript and protein levels in bronchial biopsies from a large series of patients with severe asthma, and to compare the findings with those of patients with mild to moderate asthma and healthy volunteers. Methods: Bronchoscopic study in two UK centres with real-time PCR and immunohistochemistry performed on biopsies, western blotting of bronchial epithelial cells and immunoprecipitation with anti-GRβ antibody. Measurements and main results: Protein and mRNA expression for GRα and HDAC2 did not differ between groups. GRβ mRNA was detected in only 13 of 73 samples (seven patients with severe asthma), however immunohistochemistry showed widespread epithelial staining in all groups. Western blotting of bronchial epithelial cells with GRβ antibody detected an additional 'cross-reacting' protein, identified as clathrin. HDAC1 expression was increased in patients with severe asthma compared with healthy volunteers. Conclusions: GRβ mRNA is expressed at low levels in a minority of patients with severe asthma. HDAC1 and HDAC2 expression was not downregulated in severe asthma. These data do not support upregulated GRβ and resultant reduced HDAC expression as the principal mechanism of steroid resistance in severe asthma. Conflicting GRβ literature may be explained in part by clathrin cross-reactivity with commercial antibodies.